2016
DOI: 10.1186/s12889-016-3384-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences and gender convergence in alcohol use over the past three decades (1984–2008), The HUNT Study, Norway

Abstract: BackgroundTo examine changes in men‘s and women’s drinking in Norway over a 20-year period, in order to learn whether such changes have led to gender convergence in alcohol drinking.MethodsRepeated cross-sectional studies (in 1984–86, 1995–97, and 2006–08) of a large general population living in a geographically defined area (county) in Norway. Information about alcohol drinking is based on self-report questionnaires. Not all measures were assessed in all three surveys.ResultsAdult alcohol drinking patterns ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
82
3
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 50 publications
(65 reference statements)
18
82
3
8
Order By: Relevance
“…Our findings differ from some recent research that has identified ongoing gender convergence in drinking, although many of these studies are from different settings . Alati et al .…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings differ from some recent research that has identified ongoing gender convergence in drinking, although many of these studies are from different settings . Alati et al .…”
Section: Discussioncontrasting
confidence: 99%
“…A similar pattern was found for lifetime prevalence of AUD and DUD. While the lifetime prevalence of AUD in our study was lower than that in the general Norwegian or US population, the lifetime prevalence of DUD was considerably higher (34,35,36,38).…”
Section: Discussioncontrasting
confidence: 81%
“…The higher prevalence rates of AUD and DUD in men compared to women are in accordance with gender differences in the general population (34,35,36,37). In line with others we find that women reported higher levels of hyperactivity-impulsivity (46) and ED (47) compared with men.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Esto podría explicarse por cuestiones relacionadas con diferencias en la conducta social como parte de los roles de género (Bratberg et al, 2016). Las ocasiones de consumo reducidas, no obstante, fueron la tercera razón en la muestra total, y algunos autores han alertado sobre la importancia de los motivos sociales de consumo en la adopción de patrones de ingesta de alcohol de riesgo, con diferencias según grupos culturales (Van Damme, Maes, Clays, Rosiers, Van Hal, & Hublet, 2013).…”
Section: Tabla 3 Razones Para Cambiar El Consumo De Alcohol Según Sexunclassified